Liability of country foreignness and liability of regional foreignness: Their effects on geographic diversification and firm performance - Qian, Gongming; Li, Lee; Rugman, Alan M (Journal of International Business Studies, 2013)
The costs of inter- and intra-regional diversification have been widely discussed in the existing international business literature, but the findings are mixed. Explanations for the mixed findings have important managerial implications, because business managers have to estimate accurately the costs of doing business within and across regions before they make their internationalization decisions. To explain the existing mixed findings, this study differentiates between liabilities of foreignness at the country and regional levels, and explores the joint effects of liability of country foreignness (LCF) and liability of regional foreignness (LRF) on the performance of internationalizing firms. Using data from 167 Canadian firms, we find that LCF may not necessarily be negatively correlated with intra-regional diversification, but LRF is positively correlated with inter-regional diversification. LCF moderates the relationship between LRF and inter-regional diversification, and also mediates the relationship between intra-regional diversification and firm performance. LRF mediates the relationship between inter-regional diversification and firm performance. Missing one or more of these variables may result in different cost estimates. Identification of the relationships between these variables helps to improve the accuracy of estimating the costs of doing business aboard.